Trajectories of caregiver burden in families of adult cystic fibrosis patients. Issue 6 (17th October 2017) - Wojtaszczyk, Ann; Glajchen, Myra; Portenoy, Russell K.; Berdella, Maria; Walker, Patricia; Barrett, Malcolm; Chen, Jack; Plachta, Amy; Balzano, Julie; Fresenius, Ashley; Wilder, Kenya; Langfelder-Schwind, Elinor; et al.
ABSTRACT: Objectives: Little is known about the experience of family caregivers of adults with cystic fibrosis (CF). This information is important for the identification of caregivers at risk for burden. Methods: This was a longitudinal analysis of survey data obtained from caregivers of adult CF patients participating in an early intervention palliative care trial. Caregivers completed the validated Brief Assessment Scale for Caregivers (BASC) repeatedly over a 28-month period. Mixed-effects modeling evaluated multivariate associations with positive and negative caregiver perceptions over time. Results: Of the 54 caregivers, 47.9% were spouses. The mean age was 50.9 years ( SD = 13.2); 72.2% were women; 75.9% were married; and 63.0% were employed. At baseline, the BASC revealed large variations in positive and negative perceptions of caregiving. Although average scores over time were unchanging, variation was greater across caregivers than within caregivers (0.49 vs. 0.27, respectively). At baseline, the positive impact of caregiving in the sample was higher than the negative impact. Multivariate analysis revealed that patients' baseline pulmonary function and their full-time employment status predicted caregiver burden over time. Significance of results: Caregivers of CF patients varied in their positive and negative caregiving experiences, although burden levels in individual caregivers were stable over time. When the disease was advanced, caregivers of CF patients experienced more overall burden but also more positive impact. This suggests that the role of caregivers may become more meaningful as disease severity worsens. In addition, full-time patient employment was associated with lower caregiver burden regardless of disease severity. This suggests that burden in CF caregivers may be predicted by financial strain or benefits conferred by patient employment. These associations require further investigation to determine whether highly burdened caregivers can be identified and assisted using tailored interventions.